2021
DOI: 10.52054/fvvo.13.2.014
|View full text |Cite
|
Sign up to set email alerts
|

Systematic use of transvaginal hydrolaparoscopy as a minimally invasive procedure in the exploration of the infertile patient: results and reflections

Abstract: Background: The aim of this study was to evaluate the added value of transvaginal hydrolaparoscopy (THL) in the investigation of the infertile patient. Methods: A retrospective cohort study, based on records from 01/09/2006 to 30/12/2019 was undertaken in a tertiary care infertility centre. THL was performed in 2288 patients. These were patients who were referred for endoscopic exploration of the female pelvis as part of their infertility investigation. In 374 patients with clomiphene-resistant polycystic ova… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 50 publications
0
15
1
Order By: Relevance
“…Thirty-two articles were evaluated for eligibility after abstract screening. Finally, 17 studies were included in the study [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31]. Of the 17 articles included in this review, 12 were used to provide an overview of LOD in CC-resistant patients with PCOS [16,17,[19][20][21][22][23][24][25]27,28], with some authors focusing on specific techniques in the laparoscopic field, such as Gjønnaess et al and Van Wely et al, who reported the use of ovarian electrocautery [15,23], and Duleba et al, the laparoscopic ovarian wedge resection using a harmonic scalpel [20].…”
Section: Resultsmentioning
confidence: 99%
“…Thirty-two articles were evaluated for eligibility after abstract screening. Finally, 17 studies were included in the study [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31]. Of the 17 articles included in this review, 12 were used to provide an overview of LOD in CC-resistant patients with PCOS [16,17,[19][20][21][22][23][24][25]27,28], with some authors focusing on specific techniques in the laparoscopic field, such as Gjønnaess et al and Van Wely et al, who reported the use of ovarian electrocautery [15,23], and Duleba et al, the laparoscopic ovarian wedge resection using a harmonic scalpel [20].…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, there have been numerous studies conducted, in order to determine as to whether less invasive methods might also provide useful diagnostic results. Some studies consider transvaginal hydro-laparoscopy, sometimes also called “fertiloscopy”, to be a safer, cheaper, and less invasive diagnostic method for finding pelvic adhesions [ 41 , 42 , 43 ]. In transvaginal hydro-laparoscopy, access to the Douglas pouch and, thus, to the pelvic cavity, is gained, by inserting a single-needle, dilating trocar system through the posterior fornix.…”
Section: Diagnosticsmentioning
confidence: 99%
“…The number of subtle ovarian adhesions found during transvaginal hydro-laparoscopy significantly exceeded the number of findings during standard laparoscopy (present in 12 vs. 4; absent in 9 vs. 17). Although this study has shown that transvaginal hydro-laparoscopy enables the better assessment of mild ovarian adhesions than that by standard laparoscopy [ 43 ], due to the restricted view, abdominal adhesions cannot be examined using transvaginal hydro-laparoscopy [ 46 ].…”
Section: Diagnosticsmentioning
confidence: 99%
“…KoKs 1 in the form of hysterosalpingography (HSG), is often performed. A previous study showed that a HSG with an oil-based contrast has a positive effect on the natural conception rate, compared to a HSG with water-based contrast (van Rijswijk et al, 2020). Transvaginal hydro laparoscopy (THL) is an alternative procedure to test tubal patency.…”
Section: Introductionmentioning
confidence: 99%
“…Transvaginal hydro laparoscopy (THL) is an alternative procedure to test tubal patency. The benefit of THL is the possibility to explore the tubo- ovarian structures and the pouch of Douglas, neither evaluated during a HSG ( Gordts et al, 1998 ; Gordts et al, 2021 ). However, during a THL procedure, a water-based medium (methylene blue) is used instead of an oil-based medium, of which no fertility enhancing effect has been shown.…”
Section: Introductionmentioning
confidence: 99%